2021
DOI: 10.1186/s13075-021-02511-0
|View full text |Cite
|
Sign up to set email alerts
|

Proteome study of cutaneous lupus erythematosus (CLE) and dermatomyositis skin lesions reveals IL-16 is differentially upregulated in CLE

Abstract: Background The objective of the study was to explore the disease pathways activated in the inflammatory foci of skin lesions in cutaneous lupus erythematosus (CLE) and dermatomyositis (DM). Methods Skin biopsies acquired from active CLE and DM lesions, patient (PC), and also healthy controls (HC) were investigated. Biopsy sections were examined by a pathologist, inflammatory foci were laser micro-dissected and captured, and proteins within captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Among 30 tested cytokines, IL-16 was identified among the top five and increased concentrations in the circulation were found in patients with active nephritis. Also, in another unbiased analysis of cutaneous proteome of CLE lesions, IL-16 was identified as the only cytokine differentially upregulated in CLE in comparison to dermatomyositis (DM) [ 75 ]. These findings encourage further studies on the IL-16 role in SLE.…”
Section: Il-16mentioning
confidence: 99%
“…Among 30 tested cytokines, IL-16 was identified among the top five and increased concentrations in the circulation were found in patients with active nephritis. Also, in another unbiased analysis of cutaneous proteome of CLE lesions, IL-16 was identified as the only cytokine differentially upregulated in CLE in comparison to dermatomyositis (DM) [ 75 ]. These findings encourage further studies on the IL-16 role in SLE.…”
Section: Il-16mentioning
confidence: 99%
“…ROC curve analysis also suggested that complement-associated proteins presented diagnostic performance with higher sensitivity and specificity. In addition, several studies have shown that the interaction of the complement system and interferon pathway perpetuates vascular injury. Also, both complement-dependent microangiopathy and activation of the type I IFN pathway have been shown to play major roles in DM. , A model of the interferon-complement loop was proposed in transplant-associated thrombotic microangiopathy that contributes to perpetuating vascular endothelial damage and thrombotic microangiopathy. In this model, interferons promote the expression of C1q, resulting in the activation of the classical complement pathway and the formation of MAC and endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“… 35 37 Also, both complement-dependent microangiopathy and activation of the type I IFN pathway have been shown to play major roles in DM. 38 , 39 A model of the interferon-complement loop was proposed in transplant-associated thrombotic microangiopathy that contributes to perpetuating vascular endothelial damage and thrombotic microangiopathy. In this model, interferons promote the expression of C1q, resulting in the activation of the classical complement pathway and the formation of MAC and endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…We have earlier reported increased levels of circulating IL-16 in patients with SLE and noted high levels in patients with LN 8. IL-16 was also identified as the most significantly enriched cytokine in both LE skin lesion and LN urine proteomes 9 10. IL-16 is a cytoplasmic protein cleaved by caspase-3 on various triggers.…”
Section: Introductionmentioning
confidence: 95%
“… 8 IL-16 was also identified as the most significantly enriched cytokine in both LE skin lesion and LN urine proteomes. 9 10 IL-16 is a cytoplasmic protein cleaved by caspase-3 on various triggers. After cleavage, a mature C-terminal IL-16 is secreted and involved in chemoattraction, migration and activation of CD4 T cells and may also mediate effects by binding to C-C chemokine receptor type 5 (CCR5) and CD9.…”
Section: Introductionmentioning
confidence: 99%